2016
DOI: 10.15376/biores.11.4.9219-9230
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Sulfite Concentration, Particle Size, and Reaction Time in Lignosulfonate Production from Barley Straw Using Response Surface Methodology and Artificial Neural Network

Abstract: Barley straw is a lignocellulosic biomass that can be used to obtain value-added products for industrial applications. Barley straw hydrolysis with sodium sulfite facilitates the production of lignosulfonates. In this work, the delignification process of barley straw by solubilizing lignin through sulfite method was studied. Response surface methodology and artificial neural network were used to develop predictive models for simulation and optimization of delignification process of barley straw. The influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…With improvements in computing technology, complex behavior information, such as the movement of particle groups, forces, and energy consumption during bulk material crushing, can be directly obtained from computer-aided numerical simulations and analysis with discrete element methods (DEMs) (Serna-Diaz et al 2016). DEMs have been widely used in the design and optimization of agricultural machinery.…”
Section: Introductionmentioning
confidence: 99%
“…With improvements in computing technology, complex behavior information, such as the movement of particle groups, forces, and energy consumption during bulk material crushing, can be directly obtained from computer-aided numerical simulations and analysis with discrete element methods (DEMs) (Serna-Diaz et al 2016). DEMs have been widely used in the design and optimization of agricultural machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Lignosulfonates (LS) are lignin-derived products that are present in hydrolysates generated during sulfite pretreatment (Serna-Diaz et al 2016;Dong et al 2018b;Zhou et al 2013. Despite the well-accepted concept that pretreatment hydrolysate exhibits an inhibitory role with respect to enzymes (Del Rio et al 2019;Zhong et al 2019), some studies have recently demonstrated the beneficial effects of LS on the cellulose saccharification.…”
Section: Introductionmentioning
confidence: 99%